THE INFLUENCE OF MARKETING MIX ON CUSTOMER SAVING DECISIONS AT BPRS AMPEK ANGKEK CANDUNG WEST PASAMAN BRANCH - Ningsih, Vivi Kurnia; Budiman, Fajar; Eriawati, Yossi (Transpublika Publisher, 2023)
The evolution of Islamic financial institutions and the intensifying competition between Islamic and conventional financial entities in garnering public interest for savings and fundraising, it is foreseeable that Islamic financial institutions might encounter challenges. These challenges are intrinsic to the intricate processes of creating, conveying, and delivering value to customers, as well as effectively managing customer relationships for mutual organizational and stakeholder benefits. The objective of this research is to ascertain the impact of the marketing mix on the decision-making process regarding savings at BPRS Ampek Angkek Candung West Pasaman Barat. Employing a quantitative approach along with statistical methodologies, this study investigates the interplay between the Marketing Mix (X) and Customer Decisions (Y), with 96 respondents participating. The outcomes of the hypothesis testing reveal a significance value of 0.017, which is lower than the predefined significance level (α) of 0.05 (0.017 < 0.05). This statistical finding substantiates the existence of a substantial relationship between the marketing mix and the choice to save at BPR Syariah Ampek Angkek Candung West Pasaman Barat. Consequently, it can be inferred that the marketing mix significantly contributes to the decision-making process regarding savings. This research underscores the pivotal role of strategic marketing practices in influencing customers' decisions to engage in savings activities within the context of Islamic financial institutions.